The impact of absorbable hemostatic agents on wound healing in an experimental penile fracture rat model - Mehmet Ezer; Engin Doğantekin; Muzaffer Çaydere; Aykut Koç; Çağrı Öktem; Sema Hücümenoğlu (BMC Urology)
Abstract Objective This study aimed to evaluate the effects of two absorbable hemostatic agents, oxidized regenerated cellulose (ORC) and gelatin sponge, on wound healing in a rat model of penile fracture. Materials and methods A total of 32 Wistar albino rats were divided into four groups: Control (C), Primary Suturing (PS), ORC, and Gelatin Sponge (GS). A penile fracture model was created in all rats, and wound healing was assessed histopathologically after two weeks. Key parameters assessed included primary healing, fibrosis, inflammation, and cavernous tissue healing. Results The ORC group showed significantly higher primary healing rates (100%) compared to the other groups (p < 0.01). Fibrosis was more common in the GS group (87.5%), whereas no fibrosis was observed in the ORC group (p < 0.01). In terms of cavernous tissue healing, the group treated with the ORC absorbable hemostatic agent demonstrated significantly higher healing rates compared to the control group (p = 0.000). No significant differences were observed between groups regarding inflammation. Conclusion ORC absorbable hemostatic agents significantly promote primary wound healing and reduce fibrosis in an experimental penile fracture model, whereas the gelatin sponge was associated with increased fibrosis and did not improve healing. These findings suggest that ORC may have potential clinical applications in penile fracture repair. Further clinical studies are necessary to validate these results.